Sleep pattern disturbances and associated blood pressure variations in students with overnight mobile phone usage - ANUMOL .K,; DR. J. K. MUKKADAN, (International Journal of Pharma and Bio Sciences, 2019)
Smart phone usage has become highly increasing among the teens and the youth over the past decade. They give prior importance to this media than their health and academics. Looking intently at phone, television etc. until bedtime has been reported as a cause for insomnia. The bright light rays emitting out of the mobile phones gives the brain an impression of daytime. This in turn affects the cortisol and melatonin secretions, the hormones related to sleep and wake. Thus sleep- wake cycle is interrupted. Also working overtime on this media during night cause them to displace their sleep which shows their extent of psychological dependency towards it. The mobile phones are having high rate of electromagnetic radiation which may hamper the innate rhythm of the human body. The emitting radiations along with the sleep loss may contribute to wide range of health disorders. The present study is a pilot study undertaken to compare the sleep pattern disturbances and associated blood pressure variations in students with overnight smart phone usage and controlled smart phone usage. The study groups were comprised a total of 60 samples and they were examined for 4 consecutive months for sleep pattern disturbances and blood pressure variations. The data was collected at the end of each month and data analysis was done. Our study results showed that overnight smart phone users had significant sleep pattern disturbances (p value of 0.02%) and most of the students were at borderline for hypertension while comparing with the controlled users. Previous studies also identified sleep problems in mobile phone users but, the blood pressure variations in such persons were not yet clearly identified. Hence this pilot study put forth valid evidence about the probable future health threats such as sleep disorders, hypertension among the youth who uses smart phones during night in an uncontrolled manner.